The determinants of COVID-19 vaccination intention: a meta-review - Limbu, Yam B.; Gautam, Rajesh K. (Frontiers in Public Health, 2023)
Background A large number of systematic reviews have been published that synthesized various determinants of COVID-19 vaccination intention (CVI). However, they reported inconsistent evidence. Therefore, we conducted a meta-review (systematic review of systematic reviews) to provide a comprehensive synthesis of factors influencing CVI. Methods This meta-review was conducted in accordance with PRISMA guidelines. PubMed, Scopus, Web of Science, and CINAHL were searched for systematic reviews published from 2020 to 2022 that examined the determinants of CVI. AMSTAR-2 critical appraisal tool was used to ensure the quality of included reviews, and ROBIS tool was used to evaluate the risk of bias. Results Globally, the average rate of COVID-19 vaccination intention was 56.97%. We identified 21 main determinants of CVI: socio-demographic, geographical location, social, political, government role, study timeline, attitude, perceived severity, perceived susceptibility, perceived benefits, perceived barriers, self-efficacy and perceived behavioral control, norms, trust, conspiracy theory/propaganda/misinformation, knowledge, information and communication, vaccination recommendation, vaccination history, history of COVID-19 infection, and health status and well-being. Conclusions These results suggest that COVID-19 vaccination intention is a complex process and is affected by numerous multidimensional factors. Therefore, integrated communication strategies and multifaceted interventions may be effective for improving vaccination intention against COVID-19.